Analysis of E-Module Development Needs on the Topic of Quantity and Units at High Schools in Payakumbuh - Wulandari, Dinda; Risdianto, Eko; Masito, Fitri; Setiawan, Iwan; Efendi, Rusdi (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2022)
This study has the aim of analyzing the responses of physics teachers and students to the need for developing e-modules on the amount and units of material at the SMA Negeri in Payakumbuh City. This research is part of the R & D research with the ADDIE model but is only limited to the needs analysis stage using quantitative methods. The sampling technique used was purposive sampling with data samples, namely 8 physics teachers and 250 students in 5 high schools during the covid-19 pandemic. Data collection techniques used are interviews, questionnaires and observation. The instrument used is a questionnaire on the need for e-module development for physics students and teachers. The results of this study indicate that the instruments used are valid and reliable and show that physics teachers and students strongly agree that the e-module material on quantities and units really needs to be developed to support effective online learning. Different from previous research, the update of this research was carried out in all public high schools in Payakumbuh City and focused on physics subject matter of quantities and units. This research contributes to educational practitioners so that they can develop an e-module teaching material product of magnitude and unit material for students.